(untitled) (Journal of the College of Basic Education, 2024)
The aim of the research is to identify a sample of a sample from the School of Fine Arts, a sample of (25) female students divided into two groups, one of which is experimental (11) female students and the other is control (14) female students, the achievement test. The two research groups found that the students of the first experimental group outperformed the study edition, because Gibbs’s model over the students of the control group studied according to the usual method in the test. From the success of the experiment with the research sample.